Seulimeum segment characteristic indicated by 2-D resistivity imaging method - Syukri, M.; Saad, R. (Elsevier B.V., 2017)
The study conducted at Aceh (Indonesia) within Krueng Raya and Ie Seu Um vicinity with the same geology setting (Lam Teuba volcanic), to study Seulimeum Segment characteristic using 2-D resistivity imaging method. The 2-D resistivity survey applied Pole-dipole array with minimum electrode spacing of 2 and 5 m for Ie Seu Um study area, while 10 m for Krueng Raya area. Resistivity value of Ie Seu Um study area has been correlated and validated with existing outcrops and hot springs which the value used to identify overburden, saturated area and bedrock of Krueng Raya area. The resistivity value of overburden in Krueng Raya area was identify as <30 Ohm.m, bedrock is >30 Ohm.m and saturated zone is <9 Ohm.m. The imaging results used to identify the Seulimeum segment system, where the depth is increasing from southern part (20–50 m) to northern part (50–200 m) when approaching the Andaman Sea and breaks into two sections to produce horst and graben system which indicate that it produced from the moving plat.